Assessment of the self-purification capacity of the Mooi river catchment - Mmutle, Thabang George (Central University of Technology, 2022)
Dissolved oxygen is the most essential element in natural water bodies for one of the most important reasons, namely aquatic life. This content is usually affected by the type and amount of pollution introduced in natural water bodies. The dissolved oxygen level is usually lowered at any point where a natural water body such as a river is contaminated (deoxygenation); however, using natural purification forces, rivers work hard to gain back the amount of oxygen lost in the water due to pollution (reoxygenation) This study articulated the self-purification capacity of the Mooi River catchment as a function of the rate of change of the amount of dissolved oxygen in flowing water to illustrate the purification strength of a river flow segment between sampling points. This is to subsequently present the impact of inflowing pollution from different types of adjacent sources and tributary rivers. This was achieved by conducting measurement of dissolved oxygen and temperature directly from the river, using an electrolyte dissolved oxygen meter. Respective samples (threelitre samples) were also collected at every sampling point for a biochemical oxygen demand laboratory analysis taken over five days. Using the biochemical oxygen demand and oxygen deficit analysis, deoxygenation and reoxygenation factors or constants were determined for every flow segment. The mathematical ratio between the two constants were then used to calculate the self-purification capacity of every segment. Because the hydraulic dynamics of the river also influence the strength of the river to purify itself, a reoxygenation model of hydraulic properties, such as flow velocity, hydraulic depth and radius, was developed and presented by means of a regression analysis. The findings have proven that, Mooi River’s capacity to purify itself is affected by pollution sources around it. With highest BOD values of 2.1, 2.7 and 1.5mg/l recorded during the months of November, December and January respectively, Mooi River shows to be affected more by pollution during the rainy season because of uncontrolled surface run-off wash-ins of adjacent pollution contents into the river. The high purification fluctuations were also due to the increase inhydraulic flow depth during wet season. The strength of purification for the flow segment before the Vaal River confluence (sampling point 9 and 10) is very high, which means that Mooi River does not affect Vaal River in terms of pollution conveyance. This can be clearly depicted from the positive change in dissolved oxygen deficits between sampling points 9 and 10 for the entire study period, (from 3.74 to 2.83mg/l in November), (4.44 to 3.52 in December).
Thesis (Master:Engineering:Civil)--Central University of Technology
Keywords: River catchment; Self-purification; Dissolved oxygen; Biochemical oxygen demand; Oxygen deficit; Deoxygenation; Reoxygenation; Eutrophication; Water quality modelling